(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The output of agricultural goods in the state of Haryana is significantly impacted by the city of Rewari. The area receives an estimated total of 657.3 millimetres of rainfall on a yearly basis on average. On occasion, there are issues with floods, and at other times, there is a situation of draught as a result of the uneven distribution of rainfall in the area. Because the soil in this region is composed of sandy loam, irrigating the land requires a large quantity of water. Both the ground water level and water quality in the state of Haryana, which is located in India, are topics that are covered in this article. The state of Haryana was compelled to take action when it was determined that the levels of harmful ions and microbes in certain sections of the state surpassed the maximum allowable limit for India’s drinking water. The rate of industrialization and urbanisation in Haryana has led to an all-time high in the state’s water usage, which has also reached an all-time high. It was found that the majority of the population in Haryana depends heavily on groundwater to meet their requirements, which may be attributed to the fact that surface water resources in the region are restricted and have already reached capacity. Even though its use increases crop production because it contains organic material and important nutrients for the growth, untreated sewage water still contains unwanted elements and heavy metals in it. This is the case even though it does contain important nutrients and organic material for the growth. Despite the fact that using it leads to an increase in crop output, this is still the case. It is imperative that the ground water quality be monitored at regular intervals because the human population is afflicted with a wide variety of water-borne illnesses as a direct result of the use of polluted drinking water.